2010
DOI: 10.1142/s0217984910023517
|View full text |Cite
|
Sign up to set email alerts
|

An Isoparametric Transformation-Based Interpolation-Supplemented Lattice Boltzmann Method and Its Application

Abstract: Isoparametric transformation was applied to the interpolation-supplemented lattice Boltzmann method (ISLBM). As a result, it can be applied to arbitrarily structural grids and reserve the simple procedure of ISLBM. The simulation of the lid-driven cavity flow and the flow around a cylinder were performed to validate the proposed method. The numerical results agree excellently with the data in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…There are spectral methods, mostly based on Discontinuous Galerkin (DG) methods [177][178][179][180][181][182]. Moreover, there is interpolation supplemented LBM (ISLBM) [183,184]. This technique can also be used for body-fitted structured grids (moving meshes) [185].…”
Section: Further Schemesmentioning
confidence: 99%
“…There are spectral methods, mostly based on Discontinuous Galerkin (DG) methods [177][178][179][180][181][182]. Moreover, there is interpolation supplemented LBM (ISLBM) [183,184]. This technique can also be used for body-fitted structured grids (moving meshes) [185].…”
Section: Further Schemesmentioning
confidence: 99%
“…Shyam Sunder et al [23] investigated the parallel performance of the ISLBE scheme and demonstrated that the ISLBE scheme could obtain a good parallel performance, although it increased the communication and computational time, Moreover, the generalized form of the interpolation supplemented lattice Boltzmann method (GILBM) was proposed to simulate the steady flow in generalized coordinate [24]. Qu et al [25] applied the isoparametric transformation to the ISLBE and therefore arbitrarily structural grids could be used. More recently, Zhao applied the GILBM to shallow water equations, allowing the flow problem in curved and meandering open channels to be accurately resolved based on a curvilinear coordinate grid system [26].…”
Section: Introductionmentioning
confidence: 99%